Transparent generic framing procedure (GFP) a protocol for efficient transport of block-coded data through SONET - Gorshe, S. S.; Wilson, T.
Generic framing procedure (GFP) is a new standard that has been developed to overcome data transport inefficiencies or deficiencies with the existing ATM and packet over SONET/SDH protocols. Transparent GFP (GFP-T) is an extension to GFP developed to provide efficient low-latency support for high-speed WAN applications including storage area networks. Rather than handling data on a frame-by-frame (packet-by-packet) basis, GFP-T handles block-coded (e.g., 8B/10B) character streams. This article describes the GFP protocol along with technical considerations and applications for transparent GFP.
Keywords: SONET; Block codes; Data communication; Optical fibre networks; Packet switching; Synchronous digital hierarchy; Telecommunication standards; Transport protocols; Wide area networks